Co-limitation of N and P is more prevalent in the Qinghai-Tibetan Plateau grasslands - Dong, Kai; Li, Wenjin; Tang, Yulong; Ma, Suhui; Jiang, Mengluan (Frontiers in Plant Science, 2023)
Over the past three decades, the view of nutrient limitation has transferred from single-nutrient limitation to multiple-nutrient limitation. On the Qinghai-Tibetan Plateau (QTP), many nitrogen (N) and phosphorus (P) addition experiments have revealed different N- or P-limited patterns at many alpine grassland sites, whereas it is not clear what the general patterns of N and P limitation across the QTP grasslands. We performed a meta-analysis, containing 107 publications, to assess how N and P constrained plant biomass and diversity in alpine grasslands across the QTP. We also tested how mean annual precipitation (MAP) and mean annual temperature (MAT) influence N and P limitations. The findings showed that plant biomass in QTP grasslands is co-limited by N and P. Single N limitation is stronger than single P limitation, and the combined positive effect of N and P addition is stronger than that of single nutrient additions. The response of biomass to N fertilization rate shows an increase firstly and then declines, and peaks at approximately 25 g N∙m-2∙year-1. MAP promotes the effect of N limitation on plant aboveground biomass and diminishes the effect of N limitation on belowground biomass. Meanwhile, N and P addition generally decline plant diversity. Moreover, the negative response of plant diversity to N and P co-addition is strongest than that of single nutrient additions. Our results highlight that N and P co-limitation is more prevalent than N- or P-limitation alone in alpine grasslands on the QTP. Our findings provide a better understanding of nutrient limitation and management for alpine grasslands on the QTP.